Managing oil wealth : the case of Azerbaijan - Wakeman-Linn, John. (Washington, D.C. : International Monetary Fund, 2004)
This book aims to provide a guide to the management of Azerbaijan's expected natural-resource-generated windfall, based largely on the lessons that can be drawn from the experiences----mostly negative -----of other countries.
Includes bibliographical references (p. 43-44).
aug 09/05/13
Loans
Keywords: Natural resources -- Azerbaijan -- Management; Petroleum industry and trade -- Azerbaijan